In whom we trust more? Heterogeneous effects of government assistance on trust in local officials in the Philippines - Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2021)
Given the instrumental value of trust to development, knowing what builds trust in government officials is relevant to policy. Also, establishing empirically whether satisfaction with their performances is related to public assistance could guide accountability measures to improve public service delivery. Using two rounds of nationally-representative surveys on local governance in the Philippines, we examine for the possible effects of the receipt of public assistance, which can be in cash or in kind, on trust in and satisfaction with the performances of governors, mayors, vice mayors and barangays (village) captains. To control for various sources of bias in the selection of aid recipients, we estimate treatment effects models that allow the treatment (receipt of assistance) to be exogenous or endogenous. Heterogeneous impacts are found. The receipt of assistance from any government source or a local government increases the probability of trust in the mayor, but has no effect on the probability trust in any other official. Such assistance, however, reduces the probability of satisfaction with the performance of the vice mayor. Assistance from municipal government has same negative effects for barangay captains. Public assistances do not affect the probability of trust in the governor or satisfaction with the performance of governor or mayor. The heterogeneous effects are attributed to the officials' relative reach and resources: relative to governors, mayors are more accessible to their constituents, though control less government resources; while vice mayors, barangay captains and mayors are all easily reached, the latter have greater fiscal authority and means. More than other officials, mayors draw in and provide for people who seek help or favors. The placebo test shows no impacts on the probability of satisfaction with the performance of the Department of the Interior and Local Government or of the Department Secretary, as expected.
Keywords: H31; H49; D72; 330; Government assistance; trust in officials; satisfaction with performance; treatment effects; Philippines